Complicating difficult heritage and the politics of institutionalized memory in post-Accord Colombia. (2nd January 2023) - Rodriguez Castro, Laura
ABSTRACT: The Colombian peace process with the insurgent group FARC-EP has been characterized by a lack of compliance and the politicization of peace and memory including the work of sites of memory and peace. Through complicating the European-focused concept of difficult heritage, this article presents the interventions of three museum curators and/or directors of the country's key centralized memory and peace institutions: the Memory House Museum in Medellin, the Memory Centre for Peace and Reconciliation in Bogotá and the National Centre for Historical Memory in Bogotá. Based on interviews undertaken between late 2019 and early 2020, this article reveals how those in charge of these institutions negotiate the lines between the politicization of memory and the 'alive memories' of civil society, due to the ongoing conflict. Bringing together key debates on difficult heritage and Latin American memory studies, this article seeks to contribute to Southern understandings of critical heritage and museum studies.